Activating Students' Background Knowledge and Achievement in EFL Listening Comprehension - Mahmoud, Salameh S. (American Journal of Education and Learning, 2017)
This study aims at investigating the effect of activating students' background knowledge on EFL listening comprehension. To do this, forty foundation year engineering students were assigned to two twenty-student groups: The students in the control group listened to five listening texts then answered listening comprehension questions about these texts; whereas the students in the experimental group were given pre-listening activities including pre-questions, picture discussion and pre-teaching of difficult words then listened to the same texts and answered the comprehension questions. A focus group of fifteen students from both groups were asked about their attitudes toward English listening comprehension. The “t” test analysis of the mean scores on the listening comprehension test showed statistically significant differences in favor of the experimental group. The students in the focus group showed mixed attitudes mainly negative toward listening comprehension. The research concludes with recommendations about the importance of using pre-listening activities and changing the students’ attitudes toward English language in general and listening in particular.